2019
DOI: 10.1128/aem.00641-19
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity and Sensitivity of Established and Novel Sewage-Associated Marker Genes in Human and Nonhuman Fecal Samples

Abstract: Microbial source tracking (MST) methods measure fecal contamination levels and identify possible sources using quantitative PCR (qPCR) that targets host-associated fecal microorganisms. To date, most established MST assays for human sources, especially bacterial markers, have shown some nonhuman host cross-reactions. Recently developed assays, such as the crAssphage CPQ_056, Lachnospiraceae Lachno3, and Bacteroides BacV6-21, have more limited information on host sensitivity and host specificity for human or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 49 publications
7
62
0
Order By: Relevance
“…The HPyV marker, targeting both BK and JC viruses, has shown 100% specificity for human sewage, with no cross-detection in any of the nonhuman fecal samples from Thailand (this study) or in other geographical regions (Ahmed et al, 2019a; McQuaig et al, 2009; Staley et al, 2012). Exceptions have been found only in one of 30 bird fecal samples and one of ten pig wastewater samples in Australia (Ahmed et al, 2019a, 2010).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The HPyV marker, targeting both BK and JC viruses, has shown 100% specificity for human sewage, with no cross-detection in any of the nonhuman fecal samples from Thailand (this study) or in other geographical regions (Ahmed et al, 2019a; McQuaig et al, 2009; Staley et al, 2012). Exceptions have been found only in one of 30 bird fecal samples and one of ten pig wastewater samples in Australia (Ahmed et al, 2019a, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…The HPyV marker, targeting both BK and JC viruses, has shown 100% specificity for human sewage, with no cross-detection in any of the nonhuman fecal samples from Thailand (this study) or in other geographical regions (Ahmed et al, 2019a; McQuaig et al, 2009; Staley et al, 2012). Exceptions have been found only in one of 30 bird fecal samples and one of ten pig wastewater samples in Australia (Ahmed et al, 2019a, 2010). CrAssphage showed excellent specificity in this study; however, previous reports have indicated cross-detection in one composite swine sample from earlier work in Thailand (Kongprajug et al, 2019b) and in dog, cat, gull, poultry, and cattle samples from other geographical regions (Ahmed et al, 2018b, 2018a; Stachler et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations